Artificial Intelligence Misuse and Digital Ethics Among University Students - Ratin Wahyu Juni Atma; M Zainul Hafizi; Zihori Maulida (CV. Yazri Aksara Nusantara, 2026)
The development of Artificial Intelligence (AI) in higher education presents both opportunities and digital ethical challenges among university students. This study aims to analyze the forms of AI misuse and their implications for students’ digital ethics within Indonesian online media spaces. The study employed a qualitative approach using a netnographic research design through observations of national media reports, digital documentation, and social media activities related to AI usage among university students. The findings indicate that AI misuse has developed in various forms, including AI-based plagiarism, academic dependency on automated technologies, digital identity manipulation through deepfake practices, the creation of manipulative content, and privacy violations. These phenomena are influenced by the accessibility of AI technology, limited AI literacy, weak digital ethical awareness, and the popularity-oriented culture of social media. The study also found that unethical AI usage potentially reduces academic integrity, critical thinking abilities, and the quality of students’ social interactions within digital spaces. Therefore, strengthening AI literacy, digital ethics, and institutional policies is essential to promote more responsible technology usage in higher education environments. This study contributes to the growing discourse on AI ethics and digital culture among university students in the era of digital transformation. Perkembangan kecerdasan buatan (Artificial Intelligence/AI) dalam pendidikan tinggi menghadirkan peluang sekaligus tantangan etika digital di kalangan mahasiswa. Penelitian ini bertujuan untuk menganalisis bentuk penyalahgunaan AI serta implikasinya terhadap etika digital mahasiswa dalam ruang media daring di Indonesia. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian netnografi melalui observasi terhadap pemberitaan media nasional, dokumentasi digital, dan aktivitas media sosial terkait penggunaan AI di lingkungan mahasiswa. Hasil penelitian menunjukkan bahwa penyalahgunaan AI berkembang dalam berbagai bentuk, seperti plagiarisme berbasis AI, ketergantungan akademik terhadap teknologi otomatis, manipulasi identitas digital melalui praktik deepfake, hingga pembuatan konten manipulatif dan pelanggaran privasi. Fenomena tersebut dipengaruhi oleh kemudahan akses teknologi, rendahnya literasi AI, lemahnya kesadaran etika digital, serta budaya popularitas media sosial. Penelitian ini juga menemukan bahwa penggunaan AI secara tidak etis berpotensi menurunkan integritas akademik, kemampuan berpikir kritis, serta kualitas interaksi sosial mahasiswa dalam ruang digital. Oleh karena itu, penguatan literasi AI, etika digital, dan kebijakan institusional menjadi langkah penting untuk mendorong penggunaan teknologi yang lebih bertanggung jawab di lingkungan pendidikan tinggi.